Comparison of the performance of thermoluminescence and direct ion storage dosimeters in accreditation proficiency testing. (July 2020) - Romanyukha, Alexander; Hoy, Andrew
Abstract: Results of proficiency performance testing of the direct ion storage dosimeter, MBD-1, and thermoluminescence dosimeter, Harshaw 8840/8841 are presented. The MBD-1 is a real-time, self-indicating dosimeter whereas Harshaw 8840/8841 requires a labor and time consuming processes involving Harshaw TLD reader. At certain situations both dosimeters can be worn simultaneously by personnel. Three different approaches were used for dosimeters' performance evaluation and bias calculations. The first approach (ANSI 13.11, 2009) is based on the calculation of the performance bias for each tested dosimeter with following bias averaging over all dosimeters tested in the given category. The second used approach was dose as prescribed by ISO 14146, 2018 which is not based on the performance bias calculations. The third approach is based on the linear regression of reported dose versus delivered dose data in the given category. As results of the proficiency testing we found that both dosimeters satisfy the American standard ANSI 13.11, 2009 requirements although Harshaw 8840/41 performance is significantly better. According to the International Standard ISO 14146, 2018 Harshaw 8840/8841 also passed all tested categories, whereas MBD-1 fully passed only two categories, e.g. category 1 A (accident photons) and category 5BC (neutron-photon mixtures) and fails the criterion for category 2 A (photon mixtures). Pros and contras of the used approaches and causes of the identified discrepancies are discussed. Highlights: Proficiency testing results of the direct ion storage dosimeter, MBD-1, and TLD Harshaw 8840/8841 are presented. The dosimeters were tested in three categories: Accident photons, photon mixtures and neutron-photon mixtures. Three approaches based on the ANSI 13.11, 2009, ISO 14146, 2018 and IUPAC, 1995 are used to analyze dosimeters performance. Both dosimeters passed ANSI 13.11, 2009 requirements for all tested categories. Harshaw 8840/8841 also passed ISO 14146, 2018 requirements for all categories. MBD-1 passed two categories according to the ISO 14146, 2018 but failed category of photon mixtures. Pros and contras of the used approaches and causes of the identified discrepancies are discussed.